Rede de apoio à inclusão escolar de uma estudante com paralisia cerebral: mediações de um processo colaborativo - Dounis, Alessandra Bonorandi (2019)
This study aimed to analyze the collaborative process for / in the composition of a school inclusion support network for a student with cerebral palsy as a mediation for the constitution of collective imminent development zones, re-elaboration of meanings about disability and revolutionary modification of practices. related to inclusive education. It was developed in a school of the municipal public network of Maceió where studied a student with cerebral palsy, during the 2017 and 2018 school periods. The research participants and constituents of the support network were the classroom teachers in which the student with cerebral palsy was enrolled, the respective school support professionals, the school managers, the pedagogical coordinator and the social worker, as well as a technique of the General Coordination of Special Education of the Municipal Secretary of Education of Maceió and the student's mother. The empirical material was treated from the fluctuating reading of all transcribed material and analyzes were undertaken according to the specific objectives. For the purpose of analyzing the Subjective Dimension in which constitute the meanings about the disabled person and the process of school inclusion by the participants of a network of support for inclusion, we used the procedure called Nuclei of meanings of Aguiar and Ozella (2006; 2013). Two Nuclei of meanings were systematized. The first, called “Between not believing in the possibilities of people with disabilities and allowing oneself to learn from the experience of inclusion: ‘[...] the student with this difficulty is a challenge for everyone’”, evidenced meanings about people with disabilities. disability and pedagogical practice for school inclusion that expressed fear whit the student's presence in school, doubts about their learning capacity, appreciation of health treatments, as well as questions about possible pedagogical practices for their participation in school activities. Likewise, it pointed out some changes in the meanings attributed to the student and the possibilities for their participation against the mediations of the collaboration process. The second Nuclei of meanings, entitled “Between not knowing and not having the minimum structure to deal with the inclusion of students with disabilities: the absence of theory and the scarce objective conditions for practice”, brought the theme of formation and the meanings of the participants about their ability to meet the student's pedagogical needs, from the perspective of the Medical Disability model, highlighting the contradictions between the proposal of inclusive education and the prescriptions and demands of General Education by the evaluation guidelines in the Municipal and Federal. Also highlighted the tensions generated by the school's poor material infrastructure to meet the diversity of students who were there, forcing the dichotomy between theory and practice. For the purpose of analyzing the collaborative process for the composition of the support network for school inclusion as a mediator of the constitution of collective imminent development zones and revolutions in everyday practices regarding inclusive education, were used the reflective actions of the Collaborative Research proposal of Ibiapina (2008; 2016) of description, information, confrontation and reconstruction. From the analyzes it was possible to identify the production of collective resignifications and changes in practices, confirming the thesis that, when guided by the perspectives of the Dialectical Historical Materialist Method and the Socio-Historical Psychology, the collaborative process can emerge mediations that are potent in / for the creation of collective imminent development zones and to provide modifications in the subjective dimension expressed by the meanings and transformations in the revolutionary practices of the participants in a support network for the inclusion of a student with cerebral palsy.